Elimination left recursion for E := EE+|EE-|id
How to eliminate left recursion for the following grammar?
E := EE+|EE-|id
Using the common procedure:
A := Aa|b
translates to:
A := b|A'
A' := ϵ| Aa
Applyi开发者_开发知识库ng this to the original grammar we get:
A = E, a = (E+|E-) and b = id
Therefore:
E := id|E'
E' := ϵ|E(E+|E-)
But this grammar seems incorrect because
ϵE+ -> ϵ id +
would be valid but that is an incorrect postfix expression.
Your “common procedure” is cited wrong. Taking it from the Dragon Book:
A := Aα | β
becomes
A := βA′
A′ := αA′ | ϵ
… which yields:
E := id E′
E′ := (E + | E -) E′ | ϵ
精彩评论